Sufficiently diffused attachment of nitrogen arc by gasdynamic action. Issue 6 (November 2016) - Pan, Wenxia; Chen, Lewen; Meng, Xian; Zhang, Yong; Wu, Chengkang
Abstract: For realizing diffused anode attachment in pure nitrogen arcs, a special arc plasma generator was designed and combined with suitable working parameters such as gas flow rate and arc current. The anode has a flow-restrictor channel of 2.8 mm diameter and downstream expansion half-angle of 8°, with the purpose of creating a dispersed nitrogen-arc column by strong gasdynamic expansion effect. Results show that, when thermal blocking condition existed in the flow restrictor and the cathode cavity pressure was higher than that in the exit chamber by at least 9 kPa, the action due to gasdynamic expansion could be much stronger than the self-magnetic contraction effect of the arc and the nitrogen arc column could be effectively dispersed to form a sufficiently diffused attachment on the water-cooled anode surface. Highlights: Diffused attachment of pure nitrogen arc on water-cooled anode surface. Arc channel design with a flow-restrictor and downstream expansion. Suitable combination of working parameters and the structural features of the plasma generator. Mechanism of arc dispersion through thermal blocking and downstream expansion.